Stock Price Volatility: An Efficiency Test of The Indonesian Stock Exchange In Semi-Strong Form - Mukhsin, Muhammad; Sukarno, Hari; Paramui, Hadi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
An efficient capital market is a concept in which stock prices reflect all available public information. However, the level of market efficiency varies in different countries, including Indonesia. This study aims to test semi-strong market efficiency on the Indonesia Stock Exchange (IDX) by analyzing the effect of financial and macroeconomic variables on stock prices. The study population includes all companies listed on the IDX in the 2018-2022 period. The sample was selected using purposive sampling method based on certain criteria namely issuers belonging to the primary and non-primary consumer goods sector, with a total of 174 issuers. Independent variables in this study include CR, DER, ROE, PER, Firm Size, DPR, CSR, inflation, exchange rate, and BI Rate. The dependent variable is stock price. The factor analysis method was used to reduce the independent variables into three factors: financial efficiency, corporate dimensions, and corporate external factors. Multiple regression analysis was then applied to test the effect of these three factors on stock prices. The results showed that financial efficiency factors and external factors did not have a significant influence on stock prices. However, the firm dimension factor is proven to have a significant influence on stock prices.